Evaluation of the clinical value of hematological parameters in patients with urothelial carcinoma of the bladder. Issue 14 (April 2018) - Luo, Yuzhen; Shi, Xiang; Li, Wenchao; Mo, Lijun; Yang, Zheng; Li, Xiaohong; Qin, Liuqun; Mo, Wuning
Abstract : Abstract: This study aimed to evaluate the clinical significance of pretreatment red cell distribution width (RDW), monocyte/lymphocyte ratio (MLR), neutrophil/lymphocyte ratio (NLR), and platelet/lymphocyte ratio (PLR) in patients with urothelial carcinoma of the bladder (UCB). Hematological parameters of 127 consecutive patients with UCB and 162 healthy controls were retrospectively analyzed. Receiver operating characteristic curve was plotted to determine the optimal cut-off value of RDW, MLR, NLR, and PLR to predict UCB. Whether these parameters could be independent predictors of UCB and had an association with the demographics and clinical characteristics of patients were also assessed. Patients with UCB had higher pretreatment RDW, MLR, NLR, and PLR compared with the healthy controls. With the tumor progression, MLR, NLR, and PLR rose consistently, whereas no significant difference was observed in RDW across tumor stages. NLR and PLR were associated with tumor size and tumor grade, while MLR was correlated with tumor size only. The best threshold of RDW, MLR, NLR, and PLR to predict UCB was 13.50%, 0.26, 2.16, and 128.46, respectively. Multivariate logistic regression model identified NLR ≥ 2.16 (odds ratio [OR] = 2.914; P  < .001) and PLR ≥ 128.46 (OR = 2.761; P  < .001) as independent predictors of UCB. High NLR and PLR were also associated with tumor markers, such as carcinoembryonic antigen and α-fetoprotein. Pretreatment NLR and PLR could be significant independent predictors of UCB. These simple and readily available inflammatory markers therefore might be used to manage the disease.